2018
DOI: 10.1093/schbul/sby029
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 Deficiency Modulates Adolescent Stress-Induced Dendritic Spine Loss in a Brain Region-Specific Manner and Increases Complement 4 Expression in the Hippocampus

Abstract: One neuropathological feature of schizophrenia is a diminished number of dendritic spines in the prefrontal cortex and hippocampus. The neuregulin 1 (Nrg1) system is involved in the plasticity of dendritic spines, and chronic stress decreases dendritic spine densities in the prefrontal cortex and hippocampus. Here, we aimed to assess whether Nrg1 deficiency confers vulnerability to the effects of adolescent stress on dendritic spine plasticity. We also assessed other schizophrenia-relevant neurobiological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…The data from animals stressed during the peripubertal period is also heterogenous. Our data indicating a lack of difference in the number of PV expressing interneurons in the mPFC of male mice is in agreement with studies using a combination of social isolation and forced swimming ( Page et al, 2018 ) or chronic restraint stress ( Clarke et al, 2019 ). However, another study, using a combination of physical stressors during the adolescence found a reduction in the density of PV + cells in the PrL, although only in male mice ( Page and Coutellier, 2018 ); no differences were detected in the IL cortex or when analyzing females (although the estrous cycle phase was not controlled at sacrifice).…”
Section: Discussionsupporting
confidence: 92%
“…The data from animals stressed during the peripubertal period is also heterogenous. Our data indicating a lack of difference in the number of PV expressing interneurons in the mPFC of male mice is in agreement with studies using a combination of social isolation and forced swimming ( Page et al, 2018 ) or chronic restraint stress ( Clarke et al, 2019 ). However, another study, using a combination of physical stressors during the adolescence found a reduction in the density of PV + cells in the PrL, although only in male mice ( Page and Coutellier, 2018 ); no differences were detected in the IL cortex or when analyzing females (although the estrous cycle phase was not controlled at sacrifice).…”
Section: Discussionsupporting
confidence: 92%
“…However, IFS failed to change microglial activation and levels of pro‐inflammatory cytokines and NF‐κB in amygdala in this study. This might be because of an area‐specific response to stressors (Clarke et al., 2019; Li et al., 2021; Smith et al., 2019) on the one hand and on the other hand, the results implicated that activating of microglia and releasing of pro‐inflammatory cytokines could not interpret all symptoms of PTSD.…”
Section: Discussionmentioning
confidence: 98%
“…NRG1 signaling participates in several critical neurodevelopmental processes and is implicated in nerve cell differentiation and synapse formation, radial glia formation and neuronal migration, axon navigation, and neurite outgrowth (Mei and Nave, 2014). Perturbations in NRG1/ErbB4 function have been associated with various neuropsychiatric disorders (Mei and Nave, 2014), resilience to stress (Clarke et al, 2018), and obesity/metabolic syndrome (Ennequin et al, 2015a; Salinas et al, 2016; Zeng et al, 2018; Zhang et al, 2018). Emerging evidence suggests that ErbB4 may also be important in the pathogenesis of obesity in humans (Locke et al, 2015; Salinas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in NRG1/ErbB4 function have been associated with various neuropsychiatric disorders (Mei and Nave, 2014), resilience to stress (Clarke et al, 2018), and obesity/metabolic syndrome (Ennequin et al, 2015a;Salinas et al, 2016;Zeng et al, 2018;Zhang et al, 2018). Emerging evidence suggests that ErbB4 may also be important in the pathogenesis of obesity in humans (Locke et al, 2015;Salinas et al, 2016).…”
Section: Hyper-nrg1 Conditions Attenuate Trace Fear Conditioning and mentioning
confidence: 99%
See 1 more Smart Citation